(untitled) (Journal of human and social sciences, 2019)
The United Nations has established several mechanisms to support women’s rights, reaffirming them through numerous international charters and conventions. This study examines the UN’s efforts to protect women’s rights and ensure state compliance. It is structured into three main areas: protection within UN human rights bodies, within international treaties specific to women, and through specialized international organizations. Since its founding in 1945, the UN has played a key role in promoting human rights by issuing declarations and treaties, monitoring state commitments, and preventing states from dismissing these obligations under the guise of domestic jurisdiction. Key bodies such as the General Assembly, the Economic and Social Council, the International Court of Justice, the Secretariat, and the Security Council have been entrusted with responsibilities in this field. The General Assembly, in particular, has adopted major instruments such as the Universal Declaration of Human Rights and subsequent treaties, while also recommending the ratification of the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW). These mechanisms demonstrate the UN’s ongoing role in reinforcing international respect for women’s rights and addressing violations through global cooperation.